Collective trust and normative agents - Smith, Clara Patricia
In this paper we analyze the notion of collective trust within a multi-modal setting. We argue that collective trust is a scalable concept and therefore definable in qualitatively distinct levels or strengths. We show possible connections between different forms of group trust and the emergence of obligations within groups of agents. In particular, the notion of collective trust appears to be strong enough to entail forms of delegation that may have a deontic connotation: the trust a group puts in an agent’s performance of an action yields to the result that it becomes obligatory in the interest of the group that the agent performs this action.